Heterogeneity between proximal and distal aspects of occlusive thrombi on pretreatment imaging in acute ischemic stroke. Issue 3 (June 2022) - Hashimoto, Tetsuya; Kunieda, Takenobu; Honda, Tristan; Scalzo, Fabien; Sharma, Latisha K; Hinman, Jason D; Rao, Neal M; Nour, May; Bahr-Hosseini, Mersedeh; Saver, Jeffrey L; Raychev, Radoslav; Liebeskind, David S
Background: The potential heterogeneity in occlusive thrombi caused by in situ propagation by secondary thrombosis after embolic occlusion could obscure the characteristics of original thrombi, preventing the clarification of a specific thrombus signature for the etiology of ischemic stroke. We aimed to investigate the heterogeneity of occlusive thrombi by pretreatment imaging. Methods: Among consecutive stroke patients with acute embolic anterior circulation large vessel occlusion treated with thrombectomy, we retrospectively reviewed 104 patients with visible occlusive thrombi on pretreatment non-contrast computed tomography admitted from January 2015 to December 2018. A region of interest was set on the whole thrombus on non-contrast computed tomography under the guidance of computed tomography angiography. The region of interest was divided equally into the proximal and distal segments and the difference in Hounsfield unit densities between the two segments was calculated. Results: Hounsfield unit density in the proximal segment was higher than that in the distal segment (mean difference 4.45; p  < 0.001), regardless of stroke subtypes. On multivariate analysis, thrombus length was positively correlated (β = 0.25; p  < 0.001) and time from last-known-well to imaging was inversely correlated (β = −0.0041; p  = 0.002) with the difference in Hounsfield unit densities between the proximal and distal segments. Conclusions: The difference in density between the proximal and distal segments increased as thrombi became longer and decreased as thrombi became older after embolic occlusion. This time/length-dependent thrombus heterogeneity between the two segments is suggestive of secondary thrombosis initially occurring on the proximal side of the occlusion.